Choosing wisely in burn care. Issue 5 (August 2022) - Rogers, A.D.; Amaral, A.; Cartotto, R.; El Khatib, A.; Fowler, R.; Logsetty, S.; Malic, C.; Mason, S.; Nickerson, D.; Papp, A.; Rasmussen, J.; Wallace, D.
Highlights: There are several opportunities to reduce the frequency of investigations or procedures to reduce costs and potentially prevent harm in burn care. A modified Delphi system was used by a representative group of Canadian burn surgeons to derive a series of eleven 'Choosing Wisely' statements. Nine of the statements recommend avoiding certain interventions, including prophylactic antibiotics and blood transfusions over 70g/l. Two of the statements referred unnecessary investigations, including routine daily chest X-Rays, bloodwork, or wound swabs without indication. Abstract: Background: The Choosing Wisely Campaign was launched in 2012 and has been applied to a broad spectrum of disciplines in almost thirty countries, with the objective of reducing unnecessary or potentially harmful investigations and procedures, thus limiting costs and improving outcomes. In Canada, patients with burn injuries are usually initially assessed by primary care and emergency providers, while plastic or general surgeons provide ongoing management. We sought to develop a series of Choosing Wisely statements for burn care to guide these practitioners and inform suitable, cost-effective investigations and treatment choices. Methods: The Choosing Wisely Canada list for Burns was developed by members of the Canadian Special Interest Group of the American Burn Association. Eleven recommendations were generated from an initial list of 29 statements using a modified Delphi process and SurveyMonkey™. Results: Recommendations included statements on avoidance of prophylactic antibiotics, restriction of blood products, use of adjunctive analgesic medications, monitoring and titration of opioid analgesics, and minimizing 'routine' bloodwork, microbiology or radiological investigations. Conclusions: The Choosing Wisely recommendations aim to encourage greater discussion between those involved in burn care, other health care professionals, and their patients, with a view to reduce the cost and adverse effects associated with unnecessary therapeutic and diagnostic procedures, while still maintaining high standards of evidence-based burn care.